External accelerated partial breast irradiation for ductal carcinoma in situ: long-term follow-up from a phase 3 randomized trial. Issue 3 (June 2019) - Becherini, Carlotta; Meattini, Icro; Livi, Lorenzo; Garlatti, Pietro; Desideri, Isacco; Scotti, Vieri; Orzalesi, Lorenzo; Sanchez, Luis Jose; Bernini, Marco; Casella, Donato; Nesi, Silvia; Nori, Jacopo; et al.
Introduction: For a long time, accelerated partial breast irradiation (APBI) effectiveness for ductal carcinoma in situ (DCIS) has been debated, due to conflicting published results. Recent encouraging data from phase 3 trials reopened new perspectives for this radiation approach. The aim of the present study was to analyze the long-term efficacy and safety results of the series of patients with DCIS enrolled in the APBI arm of the APBI-IMRT-Florence phase 3 trial (NCT02104895). Methods: Patients were treated in a phase 3 randomized trial comparing whole breast irradiation (50 Gy in 25 fractions to the whole breast, plus 10 Gy in 5 fractions to the tumor bed) to APBI (30 Gy in 5 nonconsecutive fractions) using the intensity-modulated radiotherapy technique. Results: Overall, 22 patients were treated in the APBI arm. Median age was 62 years (mean 59; range 42–75 years). At a median follow-up of 9.2 years (mean 8.8; range 3.8–12.1 years), no contralateral invasive/DCIS occurrence, distant metastasis, or breast cancer–related death were recorded. The 5- and 10-year local recurrence, distant metastasis–free survival, and breast cancer–specific survival were 100%. The 10-year overall survival rate was 90.9%. No late toxicity at 5 and 10 years was recorded. Conclusions: Waiting for pending studies and mature follow-up, we confirmed the efficacy and safety of APBI for low-risk DCIS.